Identifikasi Drug Related Problems Potensial Kategori Interaksi Obat pada Pasien Hipertensi di RSU Royal Prima Medan - Erida Novriani; Sintia Juniartha Purba; Vera Estefania Kaban (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Hypertension is a disease whose prevalence continues to increase from year to year, and the success of its therapy is largely determined by the appropriateness of drug selection and use. Treatment failure may occur when the chosen and administered medications do not match the patient’s condition, particularly when accompanied by drug-related problems (DRPs). Poorly controlled hypertension can lead to complications such as heart disease, kidney failure, and stroke. This study aims to identify DRPs among hypertensive patients with or without comorbidities, assessed in terms of the use of medications without indications, indications without medications, excessive dosage, insufficient dosage, and drug interactions. This research is a descriptive, non-experimental study employing a cross-sectional design with retrospective data collection among hypertensive patients with or without comorbidities at RSU Royal Prima Medan during the January–June 2025 period. The sample was selected using purposive sampling based on the inclusion criteria, resulting in a total of 135 patients.